The Effectiveness of Folk Sports Games into Kinesthetic Intelligence Curriculum in Senior Class of Kindergarten - Wanqin, Gao,; Wan Muda, W.H.N., (Journal of Social Transformation and Regional Development, 2025)
Yong children kinesthetic intelligence curriculum (KIC) is a new type of physical education curriculum which promotes the all-round development of children's physical fitness, intelligence and human ability. The purpose of this study is to determine the relationship between the application of folk sports games and the effect of KIC through the change of children's problem-solving ability. This study was conducted by quantitative method. Taking C Kindergarten in Hefei, Anhui Province, China as a sample, a quasi-experimental study was carried out in a real teaching situation and the relationship between variables was confirmed through the data differences between the experimental group and the control group. The pilot study was adopted in this study. After the formal experiment, SPSS was used for data independent sample T-test and paired sample T-test, and the relationship between the three variables was tested through data. Results after the application of folk sports games, the children's problem-solving ability and the effect of KIC were significantly improved. It can choose suitable folk sports games to be widely applied in the KIC.